6
$\begingroup$

This actually triggered me in my mind from here. After some playing around I notice that the relation $a^{\log_b x} = x^{\log_b a}$ is true for any valid value of $a,b$ and $x$. I am very inquisitive to see how this holds ?

$\endgroup$
  • $\begingroup$ Did you read Bill's answer in the question you linked? The first sentence there holds the answer to this question too. $\endgroup$ – Aryabhata Nov 18 '10 at 18:38
  • $\begingroup$ Sory,dunno why I am not getting that first line itself :( Am I such a stupid ? :( $\endgroup$ – Quixotic Nov 18 '10 at 18:44
  • $\begingroup$ What is the definition of logarithm? log_b(x) is the number which gives x when b is raised to that right? So x = b^(log_b(x)). Now use (b^m)^n = b^(mn). $\endgroup$ – Aryabhata Nov 18 '10 at 18:52
  • $\begingroup$ No Moron it's just I am being moron today, somehow it got into my mind that $r^s = b^{\log_b(r^s)} = b^{s\log_b(r)}$ holds good only when $b = e$, silly me. $\endgroup$ – Quixotic Nov 18 '10 at 18:57
  • $\begingroup$ Bill also pointed out (in parentheses) that by taking log to base b on both sides also gives you a proof and might be clearer. $\endgroup$ – Aryabhata Nov 18 '10 at 18:58
9
$\begingroup$

For any positive $r$ and any $s$, you have $$r^s = b^{\log_b(r^s)} = b^{s\log_b(r)}.$$ So, taking $r=a$ and $s=\log_b(x)$, we have: \begin{align*} a^{\log_b(x)} &= b^{\log_b(x)\log_b(a)}\\ &= b^{\log_b(a)\log_b(x)}\\ & = b^{\log_b(x^{\log_b(a)})}\\ &= x^{\log_b(a)}. \end{align*}

$\endgroup$
6
$\begingroup$

HINT $\rm\ \ \ log(A^{\log X})\ =\ log\ X\ \ log\ A\ =\ log(X^{\log A})\:,\ $ where $\rm\ log := log_b$

$\endgroup$
4
$\begingroup$

Using log properties, we have

$a^{\log_b(x)} = b^{\log_b\left(a^{\log_b(x)}\right)} = b^{\log_b(x)\log_b(a)} = \left(b^{\log_b(x)}\right)^{\log_b(a)} = x^{\log_b(a)}$

$\endgroup$
  • $\begingroup$ Did not see Arturo's answer until this was posted. $\endgroup$ – Hans Parshall Nov 18 '10 at 18:47
1
$\begingroup$

Otherwise :

Changing the base of logarithm, we have :

$$\log_{b}a= \displaystyle\frac{\log_{x}a}{\log_{x}b}$$ and $$\log_{x}b= \displaystyle\frac{\log_{b}b}{\log_{b}x} = \frac{1}{\log_{b}x} $$

By combine these two ecuations,

$\log_{b}a= (\log_{b}x)(\log_{x}a) \Leftrightarrow (\log_{b}a)(\log_{x}x)= (\log_{b}x)(\log_{x}a) \Leftrightarrow \log_{x}x^{\log_{b}a} = \log_{x}a^{\log_{b}x}$

By last, canceling $\log_{x}$ on both sides, we have : $$x^{\log_{b}a} = a^{\log_{b}x}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.